Curvature ductility prediction of reinforced high‐strength concrete beam sections - Arslan, Guray; Cihanli, Ercan (Journal of Civil Engineering and Management, 2010)
The ductility of reinforced concrete beams is very important, since it is essential to avoid a brittle failure of the structure by ensuring adequate curvature at the ultimate limit state. One of the procedures used to quantify ductility is based on curvatures, namely, curvature ductility. It is necessary to know the curvature ductility of singly reinforced high‐strength concrete (HSC) sections for determining a maximum permissible tensile reinforcement ratio or a maximum depth of the concrete compression area in design codes. The requirements of several codes and methods of prediction of the curvature ductility are based on the experimental results of normal strength concrete (NSC). The rules derived for NSC sections may not be appropriate for HSC sections, and verifications and modifications may be required for the evaluation of curvature ductility of HSC sections. In this study, the major factors affecting the curvature ductility of a singly reinforced HSC beam section are investigated. Based on numerical analyses, a parametric study has been carried out to evaluate the effects of various structural parameters on the curvature ductility of reinforced HSC beam sections.First Published Online: 10 Feb 2011